2019
DOI: 10.1007/s00384-019-03337-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for proctectomy in consecutive Crohn’s colitis surgical patients in a reference colorectal centre

Abstract: Purpose Crohn's colitis carries a risk for permanent stoma with extirpation of the rectum. We aimed to estimate the proctectomy rate and identify risk factors for proctectomy in patients with Crohn's colitis. Methods For this study, we retrospectively reviewed data from consecutive patients with Crohn's disease (CD) affecting the colon or anorectal region undergoing bowel resection in a reference colorectal centre between 2006 and 2016. The cumulative risk for proctectomy was calculated using the Kaplan-Meier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…Several reports have described the proctectomy rates after FD [10][11][12][13][14][15][16][17][18][19][20]. Generally, the proctectomy rate with or without previous FD, ranges from 19.2% to 28.8% [20][21][22][23][24]. The proctectomy rate after FD in our study was 41.3%, which was higher in comparison to previous reports (25%) [13].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Several reports have described the proctectomy rates after FD [10][11][12][13][14][15][16][17][18][19][20]. Generally, the proctectomy rate with or without previous FD, ranges from 19.2% to 28.8% [20][21][22][23][24]. The proctectomy rate after FD in our study was 41.3%, which was higher in comparison to previous reports (25%) [13].…”
Section: Discussioncontrasting
confidence: 62%
“…Furthermore, regardless of FD, studies have reported that female sex, duration of CD, history of perineal CD, smoking, and the administration of thiopurines are risk factors for proctectomy [22,24]. We believe that these risk factors require further investigation.…”
Section: Discussionmentioning
confidence: 84%